2018
DOI: 10.1016/j.amsu.2018.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Success of intraoperative imaging and management of suspected choledocholithiasis without pre-operative bile duct imaging – A case series

Abstract: BackgroundLaparoscopic common bile duct exploration (LCBDE) is gaining popularity over endoscopic retrograde cholangiopancreatography (ERCP) for the management of common bile duct stones. However, its application has been almost exclusively following preoperative stone confirmation via magnetic retrograde cholangiopancreatography (MRCP), endoscopic ultrasound (EUS) or ERCP. We present our series of LCBDE following detection of common bile duct stones with intraoperative imaging (IOI) alone, in consecutive elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It is reported that 10% ~ 20% of patients with cholecystolithiasis coexist with CBDS [ 15 ]. If the presence of CBDS can be determined before LC, the incidence of postoperative residual CBDS can be reduced [ 16 ]. The incidence of LC bile duct injury is 0.2–1.1% [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that 10% ~ 20% of patients with cholecystolithiasis coexist with CBDS [ 15 ]. If the presence of CBDS can be determined before LC, the incidence of postoperative residual CBDS can be reduced [ 16 ]. The incidence of LC bile duct injury is 0.2–1.1% [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that 10% ~ 20% of patients with cholecystolithiasis coexist with CBDS [13]. If the presence of CBDS can be determined before LC, the incidence of postoperative residual CBDS can be reduced [14]. The incidence of LC bile duct injury is 0.2-1.1% [15].…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches have been advocated in the management of CBD stones from laparoscopic single-stage CBD clearance (LCBDC) to single- and dual-stage LCBDC with intraoperative ERCP [ 66 , 67 ]. In their meta-analysis, Pan and colleagues found that LCBDC during laparoscopic cholecystectomy (LC) has superior outcomes to a preoperative ERCP sphincterotomy followed by LC and should be considered as the optimal treatment choice for CBD stones [ 67 ].…”
Section: Discussionmentioning
confidence: 99%